Caracterização geológica e modelagem 3D da mina antas norte, província Mineral de Carajás, Brasil - Paula, Rafael Nascimento (2023)
Part of the Carajás Mineral Province, the Antas Norte mine is located in the southeast portion of the Amazon Craton. The ore body lies along an NE-SW secondary shear zone and is hosted by the mafic and felsic metavolcanic rocks of the Itacaiúnas Supergroup that were, almost in their entirety, modified by alterations. Fieldwork and petrographic data made it possible to recognize an association of hydrothermal alterations that began with sodic alteration (albite) and was followed by potassic alterations (biotite + scapolite), calcic alterations (amphibole + apatite), silicification (quartz), and, finally, propylitic (chlorite + epidote + calcite). Metavolcanic rocks were altered under deformational regimes that went from ductile-brittle to brittle. Being associated with calcic alteration and occurring massively, brecciated, or in veins and venules, the mineralization of the deposit produced an ore association composed mainly of chalcopyrite, pyrrhotite, and pyrite, with ilmenite, sphalerite, and pentlandite as accessory phases. These associations of alterations and ores indicate that the hydrothermal system evolved with a decrease in temperature, salinity, and pH. Unlike other deposits that occur in Carajás, Antas Norte does not have an iron oxide phase, only iron sulfides. Given this fact, the best classification for it would be ISCG (iron sulfide copper-gold), a subtype of the large IOCG group (iron oxide copper-gold). A 3D model of the different alterations and mineralization was generated using data from 157 drill holes and 18 sections. The model revealed the importance of the shear zone for the formation of the deposit as well as the geometry of the bodies. The mineralized body has a sub-vertical tabular shape, reaching up to 350 meters in length along the strike, 200 meters in depth, and 35 meters in width. The model was also responsible for showing that the mineralization remains open at depth, requiring a greater volume of data for detail.